Proceedings of the Twenty-Second Annual Symposium on Principles of Distributed Computing 2003
DOI: 10.1145/872035.872087
|View full text |Cite
|
Sign up to set email alerts
|

Scaling properties of the Internet graph

Abstract: As the Internet grows in size, it becomes crucial to understand how the speeds of links in the network must improve in order to sustain the pressure of new end-nodes being added each day. Although the speeds of links in the core and at the edges roughly improve according to Moore's law, this improvement alone might not be enough. Indeed, the structure of the Internet graph and routing in the network might necessitate much faster improvements in the speeds of key links in the network. In this paper, using a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Apart from demonstrating the usability of our algorithms on realistic instances, our investigations also provide useful information on the similarities and differences between the topologies produced by the four different inference algorithms from Gao (2001), Subramanian et al (2002), Di Battista, Patrignani, and Pizzonia (2003), Erlebach, Hall, and Schank (2002). We believe that it is important to learn more about the characteristics of the topologies produced by different inference algorithms, as recent results about measurements on the AS level of the Internet have shown that there is a need for a simple and accurate algorithm to infer relationships; see Spring, Mahajan, and Anderson (2003) about path inflation in interand intra-domain routing, Akella et al (2003b) about multi-homing (i.e., the phenomenon that customers tend to have more than one external link to different providers, in order to guarantee the reliability of their network), and Akella et al (2003a) about scaling properties of the Internet regarding link congestion. Thus, in addition to the two connectivity measures, we study aspects such as the depth of the provider-hierarchy in the different topologies and the presence of so-called customer-provider cycles.…”
Section: Motivationmentioning
confidence: 99%
“…Apart from demonstrating the usability of our algorithms on realistic instances, our investigations also provide useful information on the similarities and differences between the topologies produced by the four different inference algorithms from Gao (2001), Subramanian et al (2002), Di Battista, Patrignani, and Pizzonia (2003), Erlebach, Hall, and Schank (2002). We believe that it is important to learn more about the characteristics of the topologies produced by different inference algorithms, as recent results about measurements on the AS level of the Internet have shown that there is a need for a simple and accurate algorithm to infer relationships; see Spring, Mahajan, and Anderson (2003) about path inflation in interand intra-domain routing, Akella et al (2003b) about multi-homing (i.e., the phenomenon that customers tend to have more than one external link to different providers, in order to guarantee the reliability of their network), and Akella et al (2003a) about scaling properties of the Internet regarding link congestion. Thus, in addition to the two connectivity measures, we study aspects such as the depth of the provider-hierarchy in the different topologies and the presence of so-called customer-provider cycles.…”
Section: Motivationmentioning
confidence: 99%
“…Edge congestion measures the amount of flows traveling through the edges of a network assuming a given traffic model and routing policy. In this study, we assume that one unit of flow between every pair of vertices is routed using the shortest-path routing policy 19,20 .…”
Section: Performance Measuresmentioning
confidence: 99%
“…Specifically, we consider the model in which each link can be replaced by multiple links (between the same pair of nodes) that can share the traffic load 8 . Ideally, we would like to provide sufficient parallel links between a pair of nodes, so that the total congestion on the corresponding edge divided equally among these parallel 8 For results on alternate methods of alleviating congestion, please refer to a full version of this paper [4]. Avg.…”
Section: Alleviating Congestion By Adding Parallel Linksmentioning
confidence: 99%